Training and Production in Research in the Educational Field: Pathways and Meanings - Turpo-Gebera, Osbaldo; Bejar, Luis Humberto; Mango-Quispe , Pedro; Araujo-Castillo, Rey; Diaz-Zavala, Rocio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This study explores education research training and its impact on scientific productivity through pathways and meanings. Interviews and narratives of 15 professors from a faculty of education at a Peruvian university undergoing research training were conducted and analyzed. The findings underscore various training avenues with a direct impact on scientific output, emphasizing a preference for collaborative publishing and the significance of scientific journals. This highlights the close interconnection between education and research in generating knowledge that addresses educational issues.